Effects of Wolbachia on mtDNA variation in two fire ant species - D. Dewayne Shoemaker; Gwen Keller; Kenneth G. Ross (Molecular Ecology, 2003)
Wolbachia are endosymbiotic bacteria that infect arthropods. As they are maternally transmitted, the spread of Wolbachia variants within host populations may affect host mtDNA evolution. We sequenced a portion of the mitochondrial cytochrome oxidase I gene from numerous individuals of two Wolbachia ‐infected fire ant species, Solenopsis invicta and S. richteri , to determine how these bacteria influence patterns of mtDNA variation. As predicted, there was a strong association between Wolbachia strain and host mtDNA lineage within and between these fire ant species. However, there was no consistent association between the presence of Wolbachia and a reduction in mtDNA diversity. Moreover, patterns of mtDNA variation within Wolbachia ‐infected populations did not differ consistently from neutral expectations, despite our prediction that strong positive selection acting on Wolbachia influences the evolutionary dynamics of other cytoplasmic genomes. Specifically, while values of Tajima's D consistently were less than zero for all six samples of fire ants harbouring Wolbachia , MacDonald–Kreitman tests suggested that the patterns of variation were different from those expected under neutrality in only two of the samples. We conclude that these neutrality tests do not unambiguously reveal a clear effect of Wolbachia infection on patterns of mtDNA variation and substitution in fire ants. Finally, consistent with an earlier study, our data revealed the presence of two divergent mtDNA haplotype lineages and Wolbachia strains within S. invicta . Recognition of these two lineages has important consequences for interpreting patterns of mtDNA evolution and genetic differentiation between conspecific social forms of this species.